Ten recommendations to improve pharmacy practice in low and middle-income countries (LMICs) - Babar, Zaheer-Ud-Din (J Pharm Policy Pract, 2021)
Medicines are important health interventions and their appropriate use could improve health outcomes. Throughout the globe, pharmacists play a very important role to improve the use of medicines. Though high-income countries are debating on futuristic approaches, independent prescribing of pharmacists, clinical skills, and to expand pharmacy services; a large majority of low and middle-income countries still lag behind to strengthen pharmacy practice. This paper presents a key set of recommendations that can improve pharmacy practice in low and middle-income countries (LMICs). The ten recommendations include (1) Mandatory presence of graduate-level pharmacists at community pharmacies (2) Clear demarcation of the roles and responsibilities of different categories of pharmacists (3) Effective categorization and implementation of medicines into (a) prescription medicines (b) pharmacists only medicines (c) over the counter medicines (4) Enforcement of laws and regulations for the sale of medicines (5) Prohibiting doctors from dispensing medicines (the dispensing separation between pharmacists and doctors). (6) Involving pharmacies and pharmacists in Universal Health Coverage Schemes to improve the affordability of medicines (7) Strengthening national medicines regulatory authorities to improve the quality, safety, and effectiveness of medicines (8) Training of pharmacists in clinical skills, vaccination, and minor ailment schemes (9) Promoting independent medicines information for consumers and healthcare professionals by developing national medicines information strategy (10) Mandatory Continuing Professional Development (CPD) programs for the Pharmacists.